Analysis of the Most Popular Study Programs at Haji University of North Sumatra Using the Decision Tree Algorithm - Dewi Sartika; Muhammad Iqbal (Sean Institute, 2025)
This study aims to analyze the clustering of the most popular study programs at Universitas Haji Sumatera Utara using the Decision Tree algorithm. This algorithm successfully grouped the study programs based on the applicants' interests, considering gender as the primary variable. The analysis results show that the most popular study programs among women are the Bachelor of Midwifery and the Bachelor of Nursing programs, which each have a very high number of female applicants. On the other hand, programs such as the Regular Bachelor of Law and Management show a more balanced interest between women and men, with Management having almost equal gender proportions. This classification model performed very well in detecting female applicants, with a high recall (95.51%) and good precision (79.84%). However, the model struggles to identify male applicants, with low recall (18.40%) and suboptimal precision (54.76%). This indicates that the model is more sensitive to predicting female applicants. Therefore, it is recommended that Universitas Haji Sumatera Utara enhance more inclusive and balanced marketing strategies, as well as optimize both regular and non-regular registration pathways to attract a more even interest from both genders, in order to achieve gender equality across various study programs and improve the efficiency of student admissions